Two Weeks of High-Intensity Interval Training in Combination With a Non-thermal Diffuse Ultrasound Device Improves Lipid Profile and Reduces Body Fat Percentage in Overweight Women - Hausswirth, Christophe; Marquet, Laurie-Anne; Nesi, Xavier; Slattery, Katie (Frontiers in Physiology, 2019)
This study evaluated the effectiveness of an innovative strategy which combined low-frequency ultra sound (LOFU) with high intensity interval training (HIIT) to improve physical fitness and promote body fat loss in overweight sedentary women. A placebo controlled, parallel group randomized experimental design was used to investigate the efficacy of a two week combined LOFU and HIIT program (3 session per week). Participants were allocated into either the Experimental HIIT group (HIITEXP, n=10) or Placebo HIIT group (HIITPLA, n=10). Baseline exercise testing (maximal oxygen uptake, lower limb strength and substrate oxidation test), dietary assessment, anthropometric measures and blood sampling were completed in week 1 and repeated in week 4 to determine changes following the program (Post-HIIT). During each training session, the HIITEXP and HIITPLA groups wore a non-thermal diffuse ultrasound belt. However, the belt was only switched on for the HIITEXP group. Delta change scores were calculated for body weight, body fat percentage (Fat%), muscle mass, V ̇O2max, hip and waist circumferences, and all lipid variables from Baseline to Post-HIIT. Statistical analysis was completed using a repeated-measures factorial analysis of variance by group (HIITPLA and HIITEXP) and time (Baseline and Post-HIIT). Results showed significant improvements in maximal oxygen uptake (HIITEXP; Baseline 24.7 ± 5.4 mL.kg-1.min-1, Post-HIIT 28.1 ± 5.5 mL.kg-1.min-1 and HIITPLA; Baseline 28.4 ± 5.9 mL.kg-1.min-1, Post-HIIT 31.4 ± 5.5 mL.kg-1.min-1) for both groups. Significant decreases in Fat% (HIITEXP; Baseline 32.7 ± 3.2%, Post-HIIT 28.9 ± 3.5% and HIITPLA; Baseline 28.9 ± 3.5%, Post-HIIT 28.9 ± 3.4% kg), waist circumference (HIITEXP; Baseline 95.8 ± 9.6 cm, Post-HIIT 89.3 ± 8.9 cm and HIITPLA; Baseline 104.3 ± 3.5 cm, Post-HIIT 103.6 ± 3.4 cm) and triglycerides (HIITEXP; -29.2%, HIITPLA; -6.7%) were observed in the HIITEXP group only. These results show that HIIT combined with LOFU was an effective intervention to improve body composition, lipid profile and fitness. This combined strategy allowed overweight, sedentary women to achieve positive health outcomes in as little as two weeks.